Answer:
80%
Step-by-step explanation:
If you divide 52 by 65 you will get a decimal, then multiply by 100% to get the equivalent.
52/65 = 0.8
0.8 x 100 = 80%
g(x) = x^2 + 1(3x - 5)
<em><u>Replace all x's with 4.</u></em>
g(4) = 4^2 + 1(3 * 4 - 5)
g(4) = 16 + 1(12 - 5)
g(4) = 17(7)
g(4) = 119 (This is your answer.)
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
Among the choices provided the answer should be letter C. Below is the solution:
top
<span>pi r^2 or pi * 400 </span>
<span>sides </span>
<span>2 pi r * 60 </span>
<span>40 * 60 pi </span>
<span>2400pi </span>
<span>so add the top and side we get p*400 + p*2400 = 2800 pi ft^2</span>
The standard deviation is 4 games
A standard deviation (or σ) is a measure of how dispersed the facts are in relation to the mean. Low general deviation method statistics are clustered around the imply, and excessive trendy deviation indicates facts are more unfold.
Don't forget the statistics set: 2, 1, 3, 2, four. The mean and the sum of squares of deviations of the observations from the mean will be 2. 4 and 5.2, respectively. as a consequence, the same standard deviation could be √(5.2/5) = 1.01.
In data, the same old deviation is a degree of the quantity of variant or dispersion of a set of values. A low preferred deviation indicates that the values tend to be close to the mean of the set, while a high general deviation shows that the values unfold out over a much broader variety.
Given that,
mean = μ = 18
standard deviation = Σ = 6
n = 2
μ x = μ = 18 games
√ x = Σ / √ = 6
√2 = 4 games
Learn more about standard deviation here brainly.com/question/12402189
#SPJ4
Step-by-step explanation:
the angle ABC = 180 - x, as ABD and ABC are complementary angles on top of the bottom line : all angles around a point on one side of a line are always adding up to 180 degrees.
but because we also know that the sum of all angles in a triangle is 180 degrees too, we can say
180 = ACB + ABC + CAB
180 = y + 180 - x + CAB
0 = y - x + CAB
x = y + CAB
x - y = CAB
therefore, the second answer option is correct.